Acompanhamento psicológico e manutenção da perda de peso após a cirurgia bariátrica do tipo bypass - Vaccaro, Regiane Valim (2018)
Obesity is a complex disease and one that is difficult to treat. The bariatric surgery has been considered the most efficient treatment for weight loss. The expectations of medicine concerning the result of bariatric surgery is to improve the patient’s quality of life, as well as his/her life expectancy through weight loss. However, this surgical method does not prevent the patient from regaining weight. The etiology of obesity is complex and multifactorial involving biological, historical, ecological, political, social economic, psychosocial and cultural aspects. The psychological aspects that intervene in bariatric surgery are related to self-image, difficulty in changing habits, eating disorders, social and family relationships, as well as low coping capacity. The current study had the objective to observe if the outcome of psychological follow-up after bariatric surgery is related to long-term weight maintenance. We use the “snowball” method to recruit participants who underwent bypass bariatric surgery 36 to 60 months prior this study. The sample consisted of men and women aged 30 to 60 years who were divided into two groups: participants who underwent psychotherapy after the surgery and those who did not. We collected data through semi-structured interviews and calculate PEP%, as approved by the Baros method, to identify positive and negative results of post-surgery weight loss. The analysis of data was carried out by using the “Discourse of the Collective Subject”. Eleven out of twenty participants underwent psychotherapy and three out of the nine who did not undergo psychological counseling believed that they should have done so. Therefore, 14 participants acknowledged the importance of psychotherapy in the treatment of obesity through bariatric surgery. PEP results did not show a significant difference between the groups. Participants' responses are in agreement with the literature by showing that psychic and emotional factors permeate the pre and post bariatric surgery treatment and that psychotherapy may contribute as a support enabling the development of greater awareness about those aspects. However, more in-depth studies and, possibly, a larger sample are needed to substantiate the contribution of psychotherapy to this process